Design analysis of potential grid connected floating photovoltaic system in UTHM - Tahir Yusuf, Ali Khalid (2020)
Every month Universiti Tun Hussein Onn (UTHM) management pays around RM 1 million for electricity bills. The aim of this project is to explore the feasibility of implementing a grid connected Floating Photovoltaic (FPV) system at the campus of UTHM. There are multiple unutilized water bodies (ponds/lakes) within the campus premises covering a total area of more than 50,000 m2. A 4000 m2 located at the lake near faculty of technical and vocational education (FPTV) is considered of the total available area for the feasibility study. A total of 1372.6 kW can be generated by deploying 335W mono crystalline PV modules with 21% efficiency on a floating mechanism (floaters) on the selected area. The FPV system is then simulated using MATLAB Simulink to observe the performance parameters of the FPV system such as total harmonic distortion (THD), current and voltage waveforms. Hybrid Optimization Model for Electric Renewable (HOMER) software has been used to obtain results such as the net present cost (NPC), cost of operation (COE), CO2 emissions impact and the payback period of the grid connected FPV system. The FPV system provides the lowest cost of energy (LCOE) RM0.418 kWh and a total net present cost (NPC) of RM 52.3 million. This system can decrease CO2 emissions by about 1241 t/yr.